Child mortality in Dublin - Grimshaw, Thomas Wrigley (Statistical and Social Inquiry Society of Ireland, 1889)
The high rate of mortality among young children as compared with the general death-rate for the whole population has attracted the attention of all vital statisticians since accurate records of births and deaths have been kept. Especial attention has been frequently called to the high death-rate among young children in Dublin, and to this subject I propose to direct special attention in the present paper. There is a popular idea that the children of the Dublin working classes met with in the slums are a healthy class, and indeed there is some ground for this view, as many active, able-bodied, handsome children?handsome even amidst dirt and rags?are certainly met with in the slums of our city. These fine healthy little creatures are, unfortunately, only the survivors, their less favourably endowed little brothers and sisters have long since passed away, and many even of those ablebodied survivors will, before they grow into adults, in their turn be gradually taken away by disease and death.
Read before the Statistical and Social Inquiry Society of Ireland, July 2nd, 1889
Keywords: Infant mortality; Dublin slums; Birth rate; Factory town; 314.15